Composite lithium supplementing material, preparation method thereof and application of the material in lithium supplementing cathode
Patent Information
- Application Number
- CN202611221129.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]为了解决目前采用的正极补锂剂,如富锂铁酸锂和富锂钴酸锂,环境稳定性较差,且在脱锂过程中释放氧气,导致出现电解液发生副反应从而影响电池性能的问题,本申请提供一种复合型补锂材料及其制备方法与在补锂正极中的应用
本申请中,通过引入纳米单质硅,并针对补锂剂和纳米单质硅一同进行碳包覆处理,一方面,可吸收补锂剂在脱锂过程中释放的氧气,抑制氧气与电解液之间的副反应、提高补锂电池的本征安全性;生成的二氧化硅产物还能与电解液中的HF反应、减少HF对正极材料的腐蚀,提升电池的循环寿命和高温性能;另一方面,还能降低脱锂电位、促进活性锂的释放,实现补锂剂高的电化学活性,同时也提高了环境稳定性,便于存储和加工。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of lithium-ion batteries, and more specifically, to a composite lithium-filling material, its preparation method, and its application in a lithium-filling cathode. Background Technology
[0002] With the rapid development of the new energy and power storage industries, the market demand for high-energy-density, long-life lithium-ion batteries is becoming increasingly urgent. In recent years, lithium replenishment technology has attracted widespread attention as one of the important means to solve the loss of active lithium in lithium-ion batteries and improve battery energy density and cycle life. Lithium replenishment is achieved by introducing an additional lithium source into the positive or negative electrode material to compensate for the irreversible capacity loss of lithium-ion batteries during formation and subsequent cycling. It is mainly divided into two directions: negative electrode pre-lithiation and positive electrode lithium replenishment. Compared with negative electrode pre-lithiation, positive electrode lithium replenishment technology is more favored by the industry due to its advantages such as high safety, simple process, and wide applicability. Currently, the positive electrode lithium replenishing agents that have been extensively researched and commercially applied mainly include lithium-rich nickel oxide, lithium-rich iron oxide, and lithium-rich cobalt oxide.
[0003] However, both lithium-rich lithium iron ore and lithium-rich lithium cobalt ore suffer from oxygen production after lithium removal, which can easily trigger side reactions in the electrolyte and affect battery performance. To solve this problem, an additional venting process is required, leading to a decrease in production efficiency. Furthermore, lithium-rich lithium nickel ore and lithium iron ore materials are highly sensitive to water and air, exhibiting poor environmental stability and significant processing challenges. Therefore, developing a cathode lithium replenishment agent that simultaneously achieves high electrochemical activity and environmental stability without gas generation is of great significance for the large-scale industrial application of cathode lithium replenishment technology. Summary of the Invention
[0004] To address the problems of poor environmental stability and the release of oxygen during delithiation, which leads to side reactions in the electrolyte and affects battery performance, the current application provides a composite lithium replenishing material, its preparation method, and its application in lithium replenishing cathodes.
[0005] Firstly, this application provides the following technical solution: A composite lithium replenishment material includes nano-elemental silicon, a lithium replenishment agent, and a carbon coating layer covering the nano-elemental silicon and the lithium replenishment agent.
[0006] In this application, nano-elemental silicon is used as a reducing agent. Its main functions are twofold: firstly, it absorbs oxygen generated during the lithium removal process of the lithium replenisher, thereby suppressing side reactions between oxygen and the electrolyte and improving the safety of the lithium-replenished battery; the silicon dioxide product formed after oxygen absorption can also react with HF in the electrolyte, reducing HF corrosion of the cathode material and improving the battery's cycle life and high-temperature performance; secondly, it lowers the lithium removal potential of the lithium replenisher, thus improving the safety and efficiency of the lithium replenishment process. If silicon dioxide is used, the silicon in it is in the tetravalent state, the highest oxidation state, which would prevent the reduction effect. By adding nano-elemental silicon as a reducing agent in this application, the lithium removal potential plateau is <4.0V, the lithium removal specific capacity is >600 mAh / g, and no gas is generated during the lithium release process.
[0007] Furthermore, the average particle size of the nano-elemental silicon is 50-600 nm.
[0008] In this application, the nano-sized elemental silicon used has a relatively uniform particle size, which can play a better role in reduction and gas generation suppression. If the particle size of the nano-sized elemental silicon used is too large, the reduction and gas generation suppression effects will be somewhat deteriorated.
[0009] Furthermore, the lithium supplement has a mass fraction of 72-91%; the nano-elemental silicon has a mass fraction of 7-24%; and the raw material for the carbon coating layer is a carbon source with a mass fraction of 2-4%.
[0010] Adding too much nano-silicon will reduce the proportion of lithium supplementer, resulting in a decrease in lithium supplementation capacity. Adding too little nano-silicon will lead to poor reduction and gas generation suppression effects.
[0011] Furthermore, the raw material for the carbon coating layer is a gaseous carbon source, which includes at least one of methane, ethylene, acetylene, benzene, carbon monoxide, ethanol, and aniline.
[0012] Furthermore, the lithium supplement is including, but not limited to, at least one of lithium iron ferrite, lithium cobalt oxide, lithium nickel oxide, and lithium oxide.
[0013] In this application, methane, ethylene, acetylene, benzene, carbon monoxide, ethanol, aniline and other gaseous carbon sources are used to deposit a dense and uniform carbon coating layer on the surface of lithium replenishment agent and nano-elemental silicon, thereby improving the electronic conductivity and environmental stability of the composite lithium replenishment material.
[0014] Secondly, this application provides the following technical solution: A method for preparing a composite lithium supplement material includes the following steps: Step 1: Grind and mix the lithium supplement and nano-elemental silicon thoroughly to obtain a mixed powder of lithium supplement and nano-elemental silicon. Step 2: After sealing, purging with inert gas and heating the mixed powder in sequence, gaseous carbon sources such as acetylene or ethanol are introduced into it. The temperature is controlled at 600-1000℃ and the pressure is 0.01-0.1 MPa to allow it to fully deposit and react for 10-30 min. Step 3: After the reaction is complete, turn off the gaseous carbon source and continue to introduce inert gas. Under the protection of the inert atmosphere, cool the reaction chamber to room temperature to obtain the composite lithium supplementation material.
[0015] In step one, the grinding process can be carried out by grinding, ball milling or sand milling. The main purpose of this operation is to fully mix the lithium replenishing agent and nano-silicon, and even achieve adhesion, so as to provide a uniform reaction substrate for the chemical vapor deposition method under high temperature conditions in step two, so that the carbon layer can be synchronously and uniformly coated on the outside of the lithium replenishing agent and nano-silicon.
[0016] In step two, under high-temperature inert atmosphere conditions, gaseous carbon sources such as methane, ethylene, acetylene, benzene, carbon monoxide, ethanol, and aniline are introduced into the reaction chamber via chemical vapor deposition (CVD). These sources undergo pyrolysis and chemical reactions, depositing a dense and uniform carbon coating layer on the surface of the lithium supplement and nano-sized elemental silicon. This enhances the material's electronic conductivity and environmental stability. Simultaneously, the low-pressure environment of 0.01-0.1 MPa facilitates achieving a thin and uniform carbon coating layer.
[0017] In step three, the gaseous carbon source is shut off and the cooling process is carried out under the protection of inert gas, which reduces the possibility of oxidation and moisture absorption due to contact with air.
[0018] The operation steps in this application are simple, efficient, fast, and environmentally friendly, and have good process controllability and scale-up adaptability, making it suitable for large-scale mass production.
[0019] Furthermore, in step one, the lithium supplement and nano-silicon are milled for 15-60 minutes.
[0020] In this application, grinding the lithium supplement and nano-elemental silicon for 15-60 minutes is beneficial for the two components to be fully mixed and adhered.
[0021] Furthermore, the heating rate in step two is 5-15℃ / min; the cooling rate in step three is 1-3℃ / min.
[0022] The heating process is relatively rapid, allowing for a quicker deposition reaction. The cooling process is relatively slow, which helps to ensure a more complete reaction, resulting in a more uniform carbon coating layer on the outside of the lithium supplement and nano-silicon, and reducing the risk of the carbon coating layer cracking due to excessively rapid cooling.
[0023] Thirdly, this application provides the following technical solution: The application of a composite lithium replenishing material in the lithium-ion battery field is described. The lithium replenishing positive electrode is prepared by fully mixing the composite lithium replenishing material, the main positive electrode material, the conductive agent, and the binder. The mass ratio of the composite lithium replenishing material to the main positive electrode material is (0.005-0.04):1.
[0024] In actual production applications, the composite lithium replenishing material is formulated with the main cathode material according to the above-mentioned ratio range. The main cathode material includes, but is not limited to, lithium iron phosphate and lithium nickel cobalt manganese oxide. This lithium replenishing cathode, combined with conductive agents and binders, is then assembled with the anode, separator, and electrolyte according to the lithium-ion battery production process. During the first charge, the battery is charged to the decomposition voltage of the composite lithium replenishing material or higher to promote the full decomposition of the lithium replenishing agent, release active lithium, and compensate for irreversible capacity loss during formation and subsequent cycling. The delithiation potential plateau is <4.0V, the delithiation specific capacity is >600 mAh / g, and no oxygen is released during the lithium release process.
[0025] In summary, this application has the following beneficial effects: In this application, by introducing nano-sized elemental silicon and subjecting both the lithium replenisher and the nano-sized elemental silicon to carbon coating treatment, on the one hand, it can absorb the oxygen released by the lithium replenisher during the delithiation process, suppress the side reaction between oxygen and electrolyte, and improve the intrinsic safety of the lithium replenishment battery; the generated silicon dioxide product can also react with HF in the electrolyte, reduce the corrosion of the cathode material by HF, and improve the cycle life and high-temperature performance of the battery; on the other hand, it can also reduce the delithiation potential, promote the release of active lithium, achieve high electrochemical activity of the lithium replenisher, and at the same time improve environmental stability, making it easier to store and process.
[0026] In this application, carbon coating of the lithium supplement for nano-elemental silicon not only enhances the conductivity of the material, but also avoids problems such as increased battery polarization, rate and low-temperature performance degradation caused by the use of lithium supplement.
[0027] In this application, a combination of physical blending and chemical vapor deposition is used to coat carbon during the preparation process. This method has advantages such as simple process, high efficiency and speed, and environmental friendliness. Moreover, the process has high controllability and scale-up adaptability, making it suitable for large-scale mass production. Attached Figure Description
[0028] Figure 1 SEM image of Example 1; Figure 2 Example 1: First constant current charge-discharge curve; Figure 3 XPS Si 2p spectra of the lithium-replenishing electrode in Example 1 before and after delithiation (a) and SEM images after delithiation (b). Figure 4Cycle performance of the battery cell used in Example 1 and the unreplenished lithium battery cell. Detailed Implementation Example
[0029] Example 1: A composite lithium supplement material, the specific preparation method of which is as follows: Step 1: Weigh 2g of lithium iron ferrite and 0.3g of nano-silicon powder with an average particle size of 100nm into an agate mortar, grind for 30min to mix them thoroughly, and obtain a mixed powder of lithium iron ferrite and nano-silicon.
[0030] Step 2: Place the above mixed powder in a tube furnace, seal it, and purge it with inert gas for 30 minutes. Then, heat it to 700°C at a heating rate of 10°C / min. Next, introduce acetylene gas into the tube furnace as a carbon source, control the pressure at 0.05 MPa, and the deposition time at 20 minutes, so that the carbon source content is 0.04 g.
[0031] Step 3: After the reaction is complete, turn off the acetylene gas and continue to purge with nitrogen. Then, under an inert atmosphere, cool the reaction chamber to room temperature at a rate of 1°C / min to obtain the carbon-coated composite lithium replenishment material.
[0032] Such as SEM photos Figure 1 As shown, this carbon-coated composite lithium supplement material has a blocky morphology, with Si particles in the form of spherical particles, and a dense carbon coating layer can be clearly observed on the surface of the material.
[0033] To test the electrochemical performance of the composite lithium replenishment material, the composite lithium replenishment material prepared in Example 1 was used as an example. positive electrode Material According to mass ratio cathode materials A positive electrode sheet was prepared using a conductive agent (carbon black) and a binder (PVDF) in a ratio of 7:2:1. This electrode sheet was used as the working electrode, and a lithium sheet as the counter electrode. Together with a separator and electrolyte, they were assembled into a coin cell half-cell in a glove box. The assembled half-cell was then subjected to a 0.05C charge-discharge performance test, with a voltage range of 2.5-4.4V. The results are as follows: Figure 2 As shown. Under these test conditions, the composite lithium replenishment material exhibits an initial charge specific capacity of 693.7 mAh / g, an initial coulombic efficiency of 1.3%, and a first delithiation potential plateau of 3.59 V, indicating that its lithium release process is irreversible and it can be used as a positive electrode lithium replenishment agent. Furthermore, as... Figure 3 As shown, the Si2p spectrum indicates that after delithiation, all silicon in the LFO / Si electrode is converted to Si. 4+ The presence of the form suggests the formation of SiO2; SEM results show that the surface of the delithiated electrode is smooth, dense, and without pores, indicating that the introduction of nano-elemental silicon reducing agent can suppress the gas production from LFO decomposition.
[0034] To verify the lithium replenishment effect of the composite lithium replenishment material, lithium iron phosphate and graphite were used as the positive and negative electrode active materials, respectively. 2.0 wt% of the composite lithium replenishment material was added during the positive electrode slurry preparation process, and a 6Ah pouch lithium-replenished battery cell was prepared according to existing procedures. For comparison, a 6Ah pouch battery cell without lithium replenishment was prepared using the same process as a control group. During the first charge, both groups of cells were charged to 4.05V at a constant current of 0.02C to promote the complete decomposition of the lithium replenishment and release of active lithium. Compared with the unreplenished group, the lithium-replenished group did not produce gas during the high-voltage stage of formation charging, and the initial discharge capacity was increased by 4.0%. Then, a room temperature 0.5C charge-1.0C discharge cycle performance test was conducted, and the results are as follows: Figure 4 As shown, after using composite lithium replenishment material, the cell capacity did not decay after 500 cycles, which is 6.5% higher than the unreplenished group. This indicates that the active lithium released by the lithium replenishment agent can be used to compensate for irreversible capacity loss during formation and subsequent cycling.
[0035] Example 2: A composite lithium supplementation material, the specific preparation method of which is as follows: Step 1: Weigh 2g of lithium cobalt oxide and 0.4g of nano-silicon powder with an average particle size of 500nm into a ball mill jar, and ball mill at 400rpm for 60min to mix them thoroughly, so as to obtain a mixed powder of lithium cobalt oxide and nano-silicon.
[0036] Step 2: Place the above mixed powder in a tube furnace, seal it, and purge it with inert gas for 50 minutes, then heat it to 800°C; then introduce ethanol gas carbon source into the tube furnace, control the pressure to be 0.08 MPa, and the deposition time to be 30 minutes, that is, the carbon source content is 0.06g.
[0037] Step 3: After the reaction is complete, turn off the ethanol gas and continue to introduce inert gas. Then, under the protection of the inert atmosphere, slowly cool the reaction chamber to room temperature to obtain the carbon-coated composite lithium supplement material.
[0038] To test the electrochemical performance of the composite lithium replenishment material, the composite lithium replenishment material prepared in this embodiment was used as the positive electrode material, and a positive electrode sheet was prepared according to the mass ratio of positive electrode material: conductive carbon black: binder PVDF = 7:2:1. The above electrode sheet was used as the working electrode, and the lithium sheet as the counter electrode. Together with the separator and electrolyte, they were assembled into a coin cell half-cell in a glove box. The assembled half-cell was then subjected to a 0.025C charge-discharge performance test, with a voltage range of 2.5-4.5V. Under these test conditions, the initial charge specific capacity of the composite lithium replenishment material was 882.5 mAh / g, the first lithium removal potential plateau was 3.22V, and the initial coulombic efficiency was 2.3%, indicating that its lithium release process is irreversible and it can be used as a positive electrode lithium replenishment agent.
[0039] To verify the lithium replenishment effect of the composite lithium replenishment material, lithium nickel cobalt manganese oxide (NCM811) and graphite were used as the positive and negative electrode active materials, respectively. 1.0 wt% of the composite lithium replenishment material was added during the positive electrode slurry preparation process, and a 4Ah pouch lithium-replenished battery cell was prepared according to existing procedures. For comparison, a 4Ah pouch battery cell without lithium replenishment was prepared using the same process as a control group. During the first charge, both groups of cells were charged to 4.2V at a constant current of 0.01C to promote the complete decomposition of the lithium replenishment and release of active lithium. Compared with the control group, the lithium-replenished group did not produce gas during the high-voltage stage of formation charging, and the initial discharge capacity increased by 4.8%. Then, a room-temperature 0.5C charge-1.0C discharge cycle performance test was conducted. After using the composite lithium replenishment material, the cell capacity did not decay after 100 cycles, which was 2.7% higher than the unreplenished group.
[0040] Example 3: A composite lithium supplement material, which differs from Example 1 in that the average particle size of the nano-elemental silicon is 50 nm.
[0041] Example 4: A composite lithium supplement material, which differs from Example 1 in that the average particle size of the nano-elemental silicon is 650 nm.
[0042] Example 5: A composite lithium replenishment material, which differs from Example 1 in that the mass fraction of the lithium replenishment agent is 72%, the mass fraction of nano-elemental silicon is 24%, and the mass fraction of the carbon source is 4%.
[0043] Example 6: A composite lithium replenishment material, which differs from Example 1 in that the mass fraction of the lithium replenishment agent is 91%; the mass fraction of nano-elemental silicon is 7%; and the mass fraction of the carbon source is 2%.
[0044] Example 7: A composite lithium replenishment material, which differs from Example 1 in that, in step two, the heating rate is 15℃ / min; and in step three, the cooling rate is 3℃ / min.
[0045] Example 8: A composite lithium replenishment material, which differs from Example 1 in that, in step two, the heating rate is 5℃ / min; and in step three, the cooling rate is 1℃ / min.
[0046] Comparative Example Comparative Example 1: A lithium supplement material, differing from Example 1 in that it does not contain nanoscale elemental silicon particles. The specific preparation method is as follows: 2g of lithium-rich lithium iron ferrite was weighed and placed in a tube furnace. After sealing and purging with inert gas for 30 minutes, the temperature was raised to 700℃. Then, acetylene gas as a carbon source was introduced into the tube furnace, with the pressure controlled at 0.05 MPa and the deposition time at 20 minutes. After the reaction was completed, the acetylene gas was turned off, while the inert gas was continued to be introduced. Then, under the protection of an inert atmosphere, the reaction chamber was slowly cooled to room temperature to obtain carbon-coated lithium supplementation material.
[0047] Using the lithium-replenishing material prepared in this comparative example as the positive electrode material, a positive electrode sheet was prepared with a mass ratio of positive electrode material: conductive carbon black: binder PVDF = 7:2:1. The above electrode sheet was used as the working electrode, and the lithium sheet as the counter electrode. Together with the separator and electrolyte, they were assembled into a coin cell half-cell in a glove box. The assembled half-cell was then subjected to a 0.05C charge-discharge performance test, with a voltage range of 2.5-4.4V. Under these test conditions, the initial charge specific capacity of the lithium-replenishing material was 565 mAh / g, the initial coulombic efficiency was 1.4%, and the first delithiation potential plateau was 3.85V. Combined with the test results of Example 1, this demonstrates that the introduction of nano-elemental silicon reducing agent can significantly reduce the delithiation potential of LFO and promote the release of active lithium.
[0048] Using lithium iron phosphate and graphite as the positive and negative electrode active materials, respectively, 2.0 wt% of the aforementioned lithium replenishing material was added during the positive electrode slurry preparation process to prepare a 6Ah soft-pack lithium-replenished battery cell according to existing procedures. For comparison, a 6Ah soft-pack battery cell without lithium replenishment was prepared using the same process as a control group. During the first charge, both groups of cells were charged to 4.05V at a constant current of 0.02C to promote the full decomposition of the lithium replenishing agent and release of active lithium. Compared with the control group, the lithium-replenished group produced more gas during the high-voltage stage of formation, resulting in a 3.2% increase in initial discharge capacity. Then, a room-temperature 0.5C charge-1.0C discharge cycle performance test was conducted. After using the lithium replenishing material, the battery cell maintained a capacity retention of 95.8% after 500 cycles, which was 2.3% higher than the un-lithiated group.
[0049] Comparative Example 2: A lithium supplement material, which differs from Example 1 in that it uses nano-silica of equal mass and the same particle size to replace nano-elemental silicon.
[0050] The first charge specific capacity, first delithiation potential plateau, and first coulombic efficiency obtained under the corresponding test conditions in Examples 1-8 and Comparative Examples 1-2 are shown in Table 1.
[0051] Table 1. Detection results of Examples 1-8 and Comparative Examples 1-2
[0052] No gas production issues occurred during the experiments in Examples 1-8.
[0053] As shown in Table 1, the initial charge specific capacity, first lithium removal potential plateau, and initial coulombic efficiency of Examples 1-8 are all superior to those of Comparative Examples 1-2. However, in Comparative Example 1, due to the absence of nano-silicon as a reducing agent, and in Comparative Example 2, the use of nano-silica instead of nano-silicon, gas generation occurred during the experiment, and the final initial charge specific capacity, first lithium removal potential plateau, and initial coulombic efficiency data were not ideal.
[0054] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A composite lithium supplementation material, characterized in that, It includes nano-elemental silicon, lithium supplement, and a carbon coating layer covering the nano-elemental silicon and lithium supplement.
2. The composite lithium supplementation material according to claim 1, characterized in that, The average particle size of the nano-elemental silicon is 50-600 nm.
3. The composite lithium replenishment material according to claim 1, characterized in that, The lithium supplement has a mass fraction of 72-91%; the nano-elemental silicon has a mass fraction of 7-24%; and the carbon coating layer is made from a carbon source with a mass fraction of 2-4%.
4. The composite lithium replenishment material according to claim 1, characterized in that, The raw material for the carbon coating layer is a gaseous carbon source, which includes at least one of methane, ethylene, acetylene, benzene, carbon monoxide, ethanol, and aniline.
5. The composite lithium supplementation material according to claim 1, characterized in that, The lithium supplement is including, but is not limited to, at least one of lithium iron ferrite, lithium cobalt oxide, lithium nickel oxide, and lithium oxide.
6. A method for preparing a composite lithium-supplementing material according to any one of claims 1-5, characterized in that, Includes the following steps: Step 1: Grind and mix the lithium supplement and nano-elemental silicon thoroughly to obtain a mixed powder of lithium supplement and nano-elemental silicon. Step 2: After sealing, purging with inert gas and heating the mixed powder in sequence, gaseous carbon sources such as acetylene or ethanol are introduced into it. The temperature is controlled at 600-1000℃ and the pressure is 0.01-0.1 MPa to allow it to fully deposit and react for 10-30 min. Step 3: After the reaction is complete, turn off the gaseous carbon source and continue to introduce inert gas. Under the protection of the inert atmosphere, cool the reaction chamber to room temperature to obtain the composite lithium supplementation material.
7. The method for preparing a composite lithium supplement material according to claim 6, characterized in that, In step one, the lithium supplement and nano-silicon are milled for 15-60 minutes.
8. The method for preparing a composite lithium supplement material according to claim 6, characterized in that, The heating rate in step two is 5-15℃ / min; the cooling rate in step three is 1-3℃ / min.
9. The application of a composite lithium-filling material in the lithium-ion battery cathode, characterized in that, A lithium-replenishing positive electrode is prepared by fully mixing the composite lithium-replenishing material, the positive electrode main material, the conductive agent, and the binder according to any one of claims 1-8, wherein the mass ratio of the composite lithium-replenishing material to the positive electrode main material is (0.005-0.04):1.